Checklist, new records, and taxonomic annotations of freshwater thecate dinoflagellate (Dinophyceae) in Colombia (2021)
A study on the freshwater dinoflagellate (Dinophyceae) of Colombia was carried out based on samples from four swamps, nine reservoirs, a small insular lake, and additional specimens deposited in the phycological collection of Universidad de Antioquia, Colombia, and the collection of Universidad de La Plata, Argentina. For most species, detailed morphological descriptions and illustrations are provided. Moreover, the geographical distribution of the species is updated. Durinskia spp., Glochidinium penardiforme, Naiadinium polonicum, Peridiniopsis elpatiewskyi, Peridiniopsis quadridens, and Sphaerodinium fimbriatum, are reported for the first time in Colombia. Furthermore, the correct sulcal plate pattern was determined for Naidinium polonicum which has been misinterpreted in earlier literature.